Solar electricity consumption, financial inclusion and welfare in sub-Saharan Africa - Dube, Andile Precious (University of the Witwatersrand, Johannesburg, 2023)
Solar electricity has continuously contributed towards alleviating energy poverty in sub- Saharan Africa. Moreover, the development of off-grid solar electricity technologies and business models that integrate mobile money into solar electricity transactions has improved access to electricity in the region. As a result, the demand and adoption of mobile money have also increased. However, existing literature has not exposed this positive development trend and other economic development opportunities inherent in solar electricity consumption. Most studies have focused on analysing the potential of solar electricity consumption in alleviating energy poverty. Although the analysis of solar electricity consumption and poverty alleviation is critical, studies have failed to extend the analysis to other economic development indicators such as financial inclusion, and money demand. This analysis is important because access to financial services and the development of financial systems in sub-Saharan Africa is low, yet economic theory postulates that renewable electricity demand induces the development of and access to financial services and increases capital stock. Therefore, it is critical to examine the broader economic opportunities inherent in solar electricity consumption to provide additional insight into development of prudent renewable energy and economic growth policies. Additionally, the extant literature fails to expose the influence of the macro-economic environment, particularly human development indicators, on the demand for solar electricity. This is important because solar electricity consumption in sub-Saharan Africa is not consistent; it is characterised by rapid fluctuations and declines in some countries. Consumer welfare (education, health, and standard of living) may influence energy consumption patterns. Therefore, this thesis provides empirical evidence of additional economic indicators that influence the demand for solar electricity to contribute to the development of effective renewable electricity policies. The thesis entails three essays that focus on the relationship between solar electricity consumption, financial inclusion, money demand and welfare. It employs a sample of 15 countries in sub-Saharan Africa for the period from 2010 to 2019 for all three essays. The first essay examines the linear and non-linear relationship between solar electricity consumption, and financial inclusion. A Financial Inclusion Index is constructed using the Principal Component Analysis. The effect of solar electricity consumption on financial inclusion is analysed using the Two-Step System Generalised Moments Method. The results show that solar electricity consumption positively influences financial inclusion, implying that solar electricity consumption is a determinant of financial inclusion in sub-Saharan Africa. Furthermore, a threshold point in the relationship between solar electricity consumption and financial inclusion is detected using the Dynamic Panel Threshold Model, and the positive effect of solar electricity consumption declines after the threshold point. The second essay examines the short-run and long-run relationship between solar electricity consumption, mobile money, and money demand in sub-Saharan Africa. It employs the dynamic panel Autoregressive Distributed Lag with Dynamic Fixed Effects and Pooled Mean Group estimators and the Dynamic Ordinary Least Squares method to check the results' robustness. The empirical results reveal that solar electricity consumption has an insignificant effect on money demand (broad money balances) in the short and long run. However, if mobile money is introduced into the money demand function, solar electricity consumption positively impacts money demand. Subsequently, the interaction of solar electricity consumption and mobile money induces an upward effect on money demand. Therefore, the findings reveal that mobile money does not moderate the effects of solar electricity consumption on money demand; instead, it increases money demand leading to adverse effects on monetary policy. It is therefore recommended that monetary authorities should monitor solar electricity expenditure to control price fluctuation and maintain financial stability, particularly in countries where the dominant payment service is mobile money. The third essay investigates the effects of welfare on solar electricity demand using the following proxies: the Human Development Index, inequality in income, government expenditure on education, infant mortality rate, and access to information and communication technology (mobile phone subscriptions and internet users). The study applied the panelquantile regression technique with nonadditive fixed effects, and the results confirmed that welfare has significant effects on solar electricity demand. It reveals that the Human Development Index, education, and infant mortality have an inverse effect on solar electricity demand. However, income inequality has a negative effect in countries with low solar electricity consumption and a positive effect in countries with median-to-high solar electricity consumption. Mobile phone subscriptions positively influence solar electricity demand in countries with low-to-median solar electricity consumption. In contrast, internet users positively affect solar electricity demand in countries with median-to-high solar electricity consumption. The findings from the first essay endorse the proposition that solar electricity consumption induces the development of and access to financial products and services (energy-finance nexus). Whereas the findings from the second essay reveal the non-moderating effect of mobile money on the relationship between solar electricity consumption and money demand. Finally, the findings from the last essay reveal that human development factors drive solar electricity consumption. It is therefore recommended that policy makers should integrate renewable electricity goals and targets into economic development policies to enhance the transition to clean electricity sources and alleviate energy poverty in sub-Saharan Africa.
Doctoral thesis submitted in fulfillment of the requirements for the award of the degree of Doctor of Philosophy in Management The Graduate School of Business Administration University of the Witwatersrand, Johannesburg 2023
Keywords: Solar electricity; Mobile money; Financial innovation financial inclusion; Money demand; Welfare; Education; Health; Mobile telephone; UCTD; SDG-7: Affordable and clean energy